2021
DOI: 10.3390/ijerph18030963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Gender-Neutral HPV Vaccination Program in Men Who Have Sex with Men (MSM)

Abstract: A major challenge in human papillomavirus (HPV) vaccine programs is the universal gender-neutral recommendation, as well as estimation of its long-term effect. The objective of this study is to predict the added benefit of male vaccination, especially in men who have sex with men (MSM), and to analyze the impact of the program on society. We propose a mathematical model of the HPV infection based on a network paradigm. Data from Spain allowed constructing the sexual network. HPV force of infection was taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Therefore, MSM who do not receive indirect protection from vaccination can only be protected by being vaccinated. 19 , 20 The HPV vaccine is effective even after the first sexual encounter. 21 , 22 Increasing vaccination coverage in the MSM population will ultimately have an important impact on reducing HPV infection in MSM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MSM who do not receive indirect protection from vaccination can only be protected by being vaccinated. 19 , 20 The HPV vaccine is effective even after the first sexual encounter. 21 , 22 Increasing vaccination coverage in the MSM population will ultimately have an important impact on reducing HPV infection in MSM.…”
Section: Introductionmentioning
confidence: 99%
“…Waning immunity was also considered to be important, especially when studying persistent HPV infection and its associated cancer incidence [31,34]. The impact of HPV vaccination was also evaluated in the population of MSM [27,[44][45][46]. Díez-Domingo et al showed that MSM would not benefit by the herd immunity effect of vaccinating females [46].…”
Section: Introductionmentioning
confidence: 99%
“…Universal vaccination of women led to a decline in the incidence of cervical disease years later [ 150 , 151 ], as well as lower HPV (HPV-6, HPV-11, HPV-16, and HPV-18) infection rates in MSW, owing to herd protection from female-only vaccination schedules [ 152 ]. However, most MSM do not benefit from this herd protection, and therefore, specific vaccination schedules have focused on this population [ 153 ]. Indeed, universal vaccination of men, regardless of their sexual behaviors, has been implemented in some countries (including the USA, France, Germany, New Zealand, and Australia) and has led to a substantial reduction in the incidence of genital warts [ 154 ].…”
Section: Hpv Vaccination In People Living With Hivmentioning
confidence: 99%